AN ANALYSIS OF STUDENT’S DIFFICULTIES IN READING COMPREHENSION (A Descriptive Study At the First Grade of SMK Negeri 1 Rasau Jaya in the Academic Year of 2022/2023) - Maria Geofany Ega; Finny Anita; Ageung Darajat (IKIP PGRI Pontianak, 2023)
The purpose of this study was to clarify what reading difficulties are in TKJ Class X students majoring in SMKN 1 Rasau Jaya and what factors cause students' reading difficulties. I. Researchers used a quantitative descriptive analysis method. The subject of this study was a class X student majoring in her TKJ at SMKN 1 Rasau Jaya. Researchers used reading tests and questionnaires as data collection techniques. The population consisted of 34 X-class students majoring in TKJ SMKN 1 Rasau Jaya, and the sample consisted of all X-class students majoring in TKJ SMKN 1 Rasau Jaya.The results of this survey show that the main difficulties faced by students are:: first, identifying references; second, identify conclusions; third, identify actual information; fourth, vocabulary; And finally show that the main idea is to understand. By using the results of a questionnaire, the researcher found that the factors that influenced students' reading difficulties were unfamiliarity with reading material, difficulties in implementing reading strategies, and limited vocabulary knowledge. The researcher concluded that students of SMKN 1 Rasau Jaya had reading comprehension difficulties due to ignorance of the material, difficulties in implementing reading strategies, and limited vocabulary knowledge. Researchers encourage teachers to develop better and more creative ways to apply technology to teach reading comprehension. This helps students overcome difficulties in understanding the material they are reading and long sentences, as well as increasing their understanding of the material being taught.Keywords: Students’Difficulties, Reading Comprehension.